Determinants of household's education and nutrition spending: A gender-based empirical analysis. Issue 4 (13th November 2017) - Kousar, Rakshananda; Sadaf, Tahira; Makhdum, Muhammad Sohail Amjad; Ijaz, Ayesha
Abstract : Purpose: This study aims to estimate the determinants of household spending on education and nutrition. Education and nutrition are noteworthy elements for human development and welfare. Separate estimates are being provided for male and female as gender determines household welfare and gender-based analysis of household spending evaluates the aptitude of decision power as well as measures their influential role in human welfare. Design/methodology/approach: Fruits, milk and dairy products are taken as proxy of substantial portion of nutrition. The study used primary urban household-level data that collected from Faisalabad city. The authors used double hurdle model. Findings: The findings of the study show that females are more likely to spend on education. Household size and number of children negatively determine the household spending on education and nutrition. Number of employed household members, level of income and education are positively associated with household spending on education and nutrition by male- and female-headed households. A very low public spending on education and nutrition have led to upsurge the hurdles of households in Pakistan. Practical implications: The study recommends that government should provide the employment opportunities, especially for females for stable and increased household income that leads to improve the household welfare. Originality/value: Several studies have examined the education spending (Mbanefoh et al ., 1997 ;Ichoku and Leibbrandt, 2003 ;Donkoh and Amikuzuno, 2011 ;Cisse, 2011 ), but these studies ignored to investigate the gender role and household spending on nutrition and education. This study is crucial in drawing suitable policy recommendations for household welfare. This study filled the gaps and scrutinized the issues that interrelated with household spending.